2006
DOI: 10.1002/elan.200603528
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Contactless Conductivity Detectors for the Determination of Small Inorganic Ions by Capillary Electrophoresis

Abstract: The analytical performance parameters of four different contactless conductivity detectors for capillary electrophoresis were determined. These detectors were designed either with a miniature cell for versatility, with high voltage excitation for high sensitivity or with a battery power supply for field application. One of the units is commercially available. The plate numbers and reproducibility of peak areas (typically about 2%) were very similar, indicating that these parameters are generally limited by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…This approach was not possible for the field instrument because of its power requirement. A comprehensive comparison between the new battery powered detector and the earlier design, as well as a commercially available unit, has been reported previously [23]. It was found that a performance in terms of precision and detection limit very similar to the other two detectors could be achieved when evaluating these on a commercial CE-instrument.…”
Section: Battery Powered Contactless Conductivity Detector and Data Amentioning
confidence: 80%
“…This approach was not possible for the field instrument because of its power requirement. A comprehensive comparison between the new battery powered detector and the earlier design, as well as a commercially available unit, has been reported previously [23]. It was found that a performance in terms of precision and detection limit very similar to the other two detectors could be achieved when evaluating these on a commercial CE-instrument.…”
Section: Battery Powered Contactless Conductivity Detector and Data Amentioning
confidence: 80%
“…This detector has previously been compared with several other contactless conductivity detectors in our laboratory and has been shown to provide the lowest LOD for inorganic ions [38]. A high-sensitivity detector head was used and this was positioned 8 cm from the outlet end of the capillary.…”
Section: Apparatusmentioning
confidence: 99%
“…Even a photothermal process has been employed for detection, combined with CCD [95]. Two recent papers deal with the CCD theory [86,96], one paper compares various CCD detectors for determination of small inorganic ions [97] and a few papers review the field [17,18,20,98].…”
Section: Low-and High-frequency Measurement Of Impedancementioning
confidence: 99%